Relativistic helitron - A. A. Kurayev; V. V. Matveyenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
This paper formulates nonlinear equations for the microwave generator of a new type - relativistic helitron and performs analysis and optimization on this basis. It is a device with centrifugal electrostatic focusing of an axisymmetric helical relativistic electron beam interacting with the Hn1 l mode of the electromagnetic field of a coaxial resonator. On the basis of numerical simulation and optimization it's shown that its efficiency exceeds the efficiency of relativistic traveling wave tube (TWT) and back wave tube (BWT).